Pengaruh Sosial Ekonomi Rumah Tangga Terhadap Minat Belajar Siswa di Sekolah SMA Negeri 1 Sibolga Kecamatan Sibolga Utara Kota Sibolga - Elvina Farida Pohan (Welfare StatE, 2013)
Against Student at State High School District I Sibolga North Sibolga Sibolga". This thesis consists of 6 chapters and 158 pages. Issue discussed here is how the socio-economic impact of households to interest high school students in the State of North Sibolga I Sibolga District Sibolga. The purpose of this study was to determine the effect of socioeconomic households to interest high school students in the State of North Sibolga I Sibolga District Sibolga. This type of research is explanatory research, which aims to look at the relationship between the variables and the research aimed to test the hypothesis that has been formulated previously. Meanwhile, data collection techniques using Product Moment Correlation technique. Conclusions based on data analysis, there is no influence of socioeconomic households to interest students in school I SMA Northern District Sibolga Sibolga. It is evident from the results of the correlation analysis performed by analyzer wherein Product Moment correlation coefficient rxy = 0.19 with a significant level of 5% is 0.25. So based on the meaning of the Product Moment Correlation, coefficient rxy of o, 19, means that the relationship between socioeconomic households (variable x) to the students' interest in school (variable y) showed a very low level of relationship. The calculations show that the socio-economic contribution of households to interest high school students in the School I Sibolga by 3.61%. Therefore, there are many other factors besides socioeconomic households contributes to greater student interest in school SMA Negeri I Sibolga Northern District Sibolga. Keywords: Socioeconomic, Student Interests